Physiological Responses of the Buffalo Syncerus caffer Culled with Succinyldicholine and Hexamethonium - J. Hattingh; V. de Vos; M.F. Ganhao; N.I. Pitts (Koedoe: African Protected Area Conservation and Science, 1988)
Physiological responses of the buffalo Syncerus caffer culled with succinyldicholine (Scoline1) are reported and it is pointed out that a number of stressors are responsible for the observed changes in blood composition. The results are compared to those obtained in a pilot experiment from buffaloes culled with Scoline and hexamethonium, a ganglion blocker. Further investigation of the effects of hexamethonium may prove it to be of benefit to animals culled with Scoline.